D Sh62 D F.,Eimplementation Of Role Play Learning In Developing Early Childhood Character In Class B At Ra Al-Istiqomah Pemenang - Fahmi, Fahmi; Marzoan, Lalu; Dwipa, Lalu Belik Made (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. This study aims to describe the implementation of role-playing learning in developing the character of early childhood students in Class B at RA Al-Istiqomah Pemenang. The research approach used is descriptive qualitative with data collection techniques including observation, interviews, and documentation. The results show that role-playing activities help develop various aspects of children's character, such as responsibility, discipline, cooperation, and honesty. Teachers act as facilitators in designing and directing role-playing activities according to the learning theme. Supporting factors include teacher creativity and active child participation, while the main obstacles are limited facilities and time. Overall, role-playing learning is proven effective in shaping positive character in early childhood.